Feed Utilisation Efficiency of Lupin Inclusion in Cobia: Role of Dietary Organic Selenium Supplementation - Pham, H.; Fotedar, Ravi; Nguyen, C.; Siddik, M. (Canadian Centre of Science and Education, 2016)
The dietary selenium (Se) requirement has been determined for cobia Rachycentron canadum using purified diet; however, its role in the utilisation of plant-derived ingredients has not been evaluated in the species. Therefore, a 3 x 2 factorial experimental design involving three inclusion levels (0, 210 and 315 g/kg) of lupin Lupinus angustifolius kernel meal (LKM) and two concentrations (0 and 0.8 mg/kg) of Se was used to evaluate the effects of Se supplementation in conjunction with LKM on the growth, feed utilisation and physiological responses in the cobia. Six isonitrogenous (46.5 % crude protein) and isoenergetic (21 MJ/kg gross energy) diets were formulated and fed to cobia for 7 weeks in a flow-through seawater system. The results showed significant effects of Se supplementation and its interaction with dietary lupin on the growth and feed efficiency of cobia. Se supplementation significantly improved the growth and feed utilisation efficiency in cobia fed lupin-based diets. The nutrient digestibility of fish fed supplemental Se lupin-based diets was significantly higher than that of fish fed diets without Se supplementation at each inclusion level of LKM. There were no significant effects of dietary Se supplementation on the survival, muscle composition or muscle amino acids, whereas regression analysis indicated a positive linear relationship between tissue Se accumulation and dietary Se levels. An enhancement of haematological responses was also observed in cobia fed Se-supplemented diets. In summary, cobia fed lupin-based diets required higher dietary Se supplementation for higher feed utilisation efficiency than previously quantified for the casein-based diet.